Walgreens Boots Alliance, Inc. : retail trade in unregulated dietary supplements - Ludwig, Carson; Wallace, Kaitlyn; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
Dietary supplements are a billion dollar unregulated industry. Walgreens Boots Alliance earns millions in revenue each year in its retail pharmacies from the sale of such supplements. Consumers who take dietary supplements often do so with the intention of protecting and improving their health. Most consider these products to be safe and free of side effects. Dietary supplements, however, can have adverse or toxic effects due to the lack of regulation surrounding ingredient labeling, level of contaminants, and consistency of ingredients across products. What obligations does Walgreens have to supervise or reveal any of this to its trusting customers?
Originally Published In Ludwig, C., Wallace, K., & O'Rourke, J. S. (2019). Walgreens Boots Alliance, Inc.: Retail Trade in Unregulated Dietary Supplements. 19-21. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Walgreens (Firm) -- Customer services; Walgreens (Firm) -- Public relations; Dietary supplements industry; Dietary supplements -- Safety regulations